Unemployment benefits and activation in federal welfare states: An institutional moral hazard perspective. Issue 5 (20th October 2021) - Luigjes, Christiaan; Vandenbroucke, Frank
ABSTRACT: Subnational governments have become more involved in the 'regulation of unemployment' (the design, implementation and financing of unemployment-related benefits and activation), partly because they are thought to be better placed to activate the unemployed than federal governments. However, depending on its specific design, decentralization can reduce the incentives subnational governments have to implement effective activation. Such 'institutional moral hazard' is not yet systematically theorized. We examine how and to what extent it affects three federal countries. We distinguish three factors that influence whether institutional moral hazard is perceived as a problem and how it can be resolved. We identify two types of subnational challenges to federal control.